MicroRNA-892a regulates laryngocarcinoma cell proliferation via Dicer. Issue 14 (August 2020) - Dong, Jinhui; Wang, Jianxing; Shan, Chunguang; Zhang, Haizhong; Xu, Ou
MicroRNA (miR) plays a critical role in the progression of multiple malignancies. Nevertheless, knowledge of the role it plays in laryngeal cancer is limited. In this study, we explored the role of miR-892a in laryngeal cancer cell proliferation and apoptosis. miR-892a expression was increased in 17 laryngeal cancer samples and cells compared with that in healthy tissues, laryngeal cancer normal surrounding tissues, and the NP69 human nasopharyngeal epithelial cell line. Conversely, Dicer expression was downregulated in human laryngeal cancer samples as well as in the laryngeal cancer cell lines. CCK-8 assays and colony formation assay confirmed that depleted miR-892a expression damaged the proliferation and growth of TU212 and M4E cells. Annexin V/PI flow cytometry displayed that miR-892a inhibition led to increased apoptosis of TU212 and M4E cells. By conducting bioinformatic analysis and dual-luciferase reporter assay, it was revealed that that miR-892a targets Dicer 3′-UTR for silencing. Dicer expression inhibition offsets the effect of miR-892a on the growth and apoptosis of laryngeal cancer cells. Dicer overexpression displayed similar phenotype with miR-892a inhibition on the properties of laryngeal cancer cells. Results of in vivo experiments further confirmed that miR-892a silencing suppressed tumor growth in a mouse model. Hence, the results of this study provide new ideas about the biological and molecular mechanisms behind laryngeal cancer progression, thereby obtaining novel laryngeal cancer treatments. Impact statement: This work expanded the knowledge of the molecular mechanisms underlying LC progression by exploring the role of miR-892a in the viability of TU212 and M4E cells. The results showed that miR-892a, which exhibited elevated expression in LC cells and tissue specimens of patients with LC, exerted an inhibitory effect on Dicer expression, whereas silencing of miR-892a in TU212 and M4E cells hindered cell proliferation and growth and promoted apoptosis. Furthermore, miR-892a was demonstrated to directly target Dicer 3′-UTR and inhibit its expression. These findings demonstrated that miR-892a acted as an LC oncogene via its action on Dicer, which further confirmed that miR-892a can serve as a diagnostic indicator or promising agent for LC treatment.